2020
DOI: 10.3390/app10196634
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on Two Types of OSB Boards Obtained from Mixed Resinous and Fast-growing Hard Wood

Abstract: The paper aims to compare the oriented strand boards (OSBs) made in the laboratory from a mixture of softwood species to those made from hardwood species, followed by their comparison to European and industry standards. In this regard, the main properties of the panels made in the laboratory were determined, including density, absorption, and swelling in thickness, modulus of elasticity, modulus of rupture, and internal bond. The analysis of the properties of swelling (24 h) and absorption (24 h) revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Several studies on OSB made from combination raw material have been conducted and showed good OSB properties (Amusant et al 2009;Arnould et al 2010;Febrianto et al 2010;Bufalino et al 2015;Suhadi et al 2018;Lunguleasa et al 2020). However, to date, information on the preparation conditions and properties of three-layer BOSBs from different bamboo species, specifically for each layer, has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on OSB made from combination raw material have been conducted and showed good OSB properties (Amusant et al 2009;Arnould et al 2010;Febrianto et al 2010;Bufalino et al 2015;Suhadi et al 2018;Lunguleasa et al 2020). However, to date, information on the preparation conditions and properties of three-layer BOSBs from different bamboo species, specifically for each layer, has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…OSB is extensively used for wall sheathing, floor underlayment, roof cover and I-joist in both commercial and residential building. OSB also is used in furniture, reels, trailer liners and recreational vehicle floors [71][72][73].…”
Section: Oriented Strand Board (Osb)mentioning
confidence: 99%
“…Since OSBs and plywood are wood-based composites, OSBs are susceptible to ignition [42], and there is a need for an additional fire protection layer. OSBs are composite multilayer boards made of wood strands with a specific shape, thickness, and adhesive strength [43,44] which are very similar to plywood, with the only significant difference being the price. This has led to OSB panels replacing plywood in the construction sector [45].…”
Section: Sheathing Boards and Finishing Layersmentioning
confidence: 99%